2023
DOI: 10.1007/s12029-022-00899-9
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Type of Adjuvant Chemotherapy Among Stage III Colon Cancer Patients in England

Abstract: Purpose: Treatment with any adjuvant chemotherapy for Stage III colon cancer has been shown to differ between groups. Few studies, however, explore variations in the type of adjuvant chemotherapy received, none of which from the UK. The aim of this study is to explore variation in the type of chemotherapy received by Stage III colon cancer patients. Methods: Data from the national cancer registry was linked to the Systemic Anti-Cancer Therapy database, which provides detailed information on treatment of malign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Five of the six studies evaluating the use of adjuvant chemotherapy demonstrated inequalities 24 44 45 50 51. Meanwhile, both studies evaluating the use of palliative chemotherapy demonstrated similar inequalities 24 46.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Five of the six studies evaluating the use of adjuvant chemotherapy demonstrated inequalities 24 44 45 50 51. Meanwhile, both studies evaluating the use of palliative chemotherapy demonstrated similar inequalities 24 46.…”
Section: Resultsmentioning
confidence: 92%
“…The system interval was examined in 12 studies, with 7 different time points evaluated, summarised in figure 2 12–23. In total, 15 studies reported the receipt of surgery,19 20 24–36 7 studies evaluated surgical variation,37–43 14 studies reported the receipt of chemotherapy,19 20 24–27 44–51 7 reported the receipt of radiotherapy19 20 25–27 43 52 and 2 reported the receipt of any treatment 17 46…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations